Oxygen-doped TiZr-based single-phase refractory high-entropy alloy and preparation method thereof
Through oxygen doping and suitable element composition, combined with large plastic deformation and medium temperature tempering treatment, the problem of difficulty in taking into account the strength and plasticity of refractory high-entropy alloys is solved, and a TiZr-based single-phase refractory high-entropy alloy with ultra-high strength and good plasticity is prepared.
Patent Information
- Application Number
- CN202411907489.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
Smart Images

Figure CN119710423A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of refractory high entropy alloys, and in particular relates to an oxygen-doped TiZr-based single-phase refractory high entropy alloy and a preparation method thereof. Background Art
[0002] Refractory high entropy alloys are expected to become new aerospace engine materials and nuclear reactor materials due to their high strength, high hardness, low neutron cross section, high wear resistance, and excellent oxidation resistance and high temperature creep resistance. TiZr-based refractory high entropy alloys have excellent room temperature plasticity and have received widespread attention, but their strength is usually lower than 1GPa. How to significantly increase the strength while maintaining a certain plasticity is a challenge. Common alloy strengthening methods such as precipitation strengthening, solid solution strengthening, and deformation strengthening are also applicable to refractory high entropy alloys. For example, adding 7.5% Al to TiZrNb can increase the strength from 680MPa to 930MPa, which is due to the B2 phase strengthening caused by Al addition; adding 500ppm B to TiZrNb can increase the strength from 621MPa to 739MPa; AlMoNbHfTi can obtain a strength of 1.2GPa through cold rolling deformation.
[0003] However, these strengthening measures are usually accompanied by an inevitable decrease in plasticity, because both the second phase and the interstitial atoms play a role in pinning dislocations during deformation. The large accumulation of dislocations leads to stress concentration, which acts as a crack source under the action of external loads and causes premature fracture of the material. How to break the strength-plasticity strategy is a difficult problem.
[0004] In recent years, studies have found that doping oxygen in refractory high-entropy alloys can improve strength while rarely compromising plasticity. This is because the ordered oxygen complexes generated by adding oxygen can promote dislocation cross-slip while hindering dislocation movement, thereby achieving the goal of balancing strength and plasticity. However, these single strengthening methods have limited strengthening effects, which makes it difficult to prepare ultra-high strength refractory high-entropy alloys. Therefore, it is crucial to significantly improve strength while retaining some room temperature plasticity for the preparation of ultra-high strength refractory high-entropy alloys. Summary of the invention
[0005] The purpose of the present invention is to provide an oxygen-doped TiZr-based single-phase refractory high-entropy alloy and a preparation method thereof, so as to solve the problem that it is difficult to prepare ultra-high strength refractory high-entropy alloys by a single strengthening method.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] The present invention provides an oxygen-doped TiZr-based single-phase refractory high-entropy alloy, which comprises Ti, Zr, Nb, V and O elements, wherein the sum of the atomic contents of the Ti, Zr, Nb and V elements is equal to 100%, and the atomic contents of the Ti, Zr, Nb and V elements satisfy Ti≥Zr>Nb>V.
[0008] As a further optimization scheme of the present invention, the Ti, Zr, Nb, and V elements are calculated according to atomic percentage, with Ti element being 25at.%-40at.%, Zr element being 25at.%-40at.%, Nb element being 15at.%-30at.%, and V element being 5at.%-15at.%. Specifically, the contents of Ti and Zr are increased to obtain large lattice distortion and accommodate more oxygen atoms. Too high a Nb content will greatly increase the density of the alloy, while too low a Nb content will be unfavorable for the formation of a single-phase body-centered cubic structure, so 15at.%-30at.% is selected. V has a good strengthening effect, but when the content is higher than 15%, it is easy to precipitate a precipitate phase at the grain boundary, reducing plasticity, so the content is controlled at 5at.%-15at.%.
[0009] Furthermore, the atomic content of each element Ti, Zr, Nb, and V ranges from 35 at.%, 30 at.%, 25 at.%, and 10 at.%, respectively.
[0010] As a further optimization scheme of the present invention, in step 1, the oxygen doping method is to use TiO 2 The atomic content of oxygen added to the alloy is 1 at.%-2 at.%, because the strengthening effect of low oxygen content is limited, and too high oxygen content will lead to alloy brittleness.
[0011] As a further optimization scheme of the present invention, the oxygen-doped TiZr-based single-phase refractory high-entropy alloy is prepared by first smelting raw materials containing Ti, Zr, Nb, V and O elements to obtain an alloy ingot, and then subjecting the alloy ingot to large plastic deformation treatment and medium-temperature tempering treatment.
[0012] The present invention also provides a method for preparing an oxygen-doped TiZr-based single-phase refractory high-entropy alloy, comprising the following steps:
[0013] Step 1: Design the atomic content of each element Ti, Zr, Nb, V and the atomic content of the doped oxygen element in the alloy, and then weigh the raw materials according to the designed atomic content of each chemical element;
[0014] Step 2: Smelting the raw materials weighed in step 1 to obtain an oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot;
[0015] Step 3: performing large plastic deformation treatment on the oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot obtained in step 2;
[0016] Step 4: performing medium-temperature tempering treatment on the oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot obtained by the treatment in step 3.
[0017] As a further optimization scheme of the present invention, the step three is specifically as follows: first, the oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot is cut into a rectangular shape by wire cutting to obtain a rectangular alloy sample, and then, the rectangular alloy sample is subjected to a small amount of multiple cold rolling deformation treatments at room temperature, and each deformation amount is not higher than 20%.
[0018] As a further optimization scheme of the present invention, in step three, the total thinning amount of the sample after cold rolling is 20%-90% of the thickness of the original sample.
[0019] As a further optimization scheme of the present invention, in the step 4, the temperature range of the medium-temperature annealing treatment is 600°C-800°C, and the time is 10min-30min. Under this process condition, the alloy ingot undergoes dislocation recovery while avoiding complete recrystallization, thereby obtaining a refractory high-entropy alloy with both room temperature strength and toughness.
[0020] The beneficial effects of the present invention are:
[0021] (1) The oxygen-doped TiZr-based single-phase refractory high-entropy alloy prepared by the preparation method of the present invention has, first, a greatly improved strength, which can reach above 1.4 GPa, and can reach a maximum of ~1.8 GPa by adjusting the oxygen content and the degree of deformation; second, it has a certain room temperature plasticity, and while greatly improving the strength, it still maintains a room temperature plasticity of >10%, achieving a balance between strength and plasticity at room temperature.
[0022] (2) The preparation method provided by the present invention is simple and easy to implement, and does not require complicated deformation processing and aging treatment. Simple melting combined with cold rolling deformation can significantly improve the mechanical properties of refractory high entropy alloys.
[0023] (3) The oxygen-doped TiZr-based single-phase refractory high-entropy alloy prepared by the present invention has a density of only about 6.3 g / cm 3 It is much lower than most refractory high-entropy alloys and is lighter. The low density enables the alloy to have a higher specific yield strength (yield strength / density) at the same yield strength, and has good application prospects in fields such as aerospace engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is Ti in Example 1 of the present invention 35 Zr 30 Nb 25 V10 XRD patterns of alloys and alloys with different oxygen contents;
[0025] Figure 2 is Ti in Example 1 of the present invention 35 Zr 30 Nb 25 V 10 Room temperature tensile curves of alloy samples;
[0026] Figure 3 is Ti in Example 1 of the present invention 35 Zr 30 Nb 25 V 10 -1O、Ti 35 Zr 30 Nb 25 V 10 -1O-20CR and Ti 35 Zr 30 Nb 25 V 10 -Tensile stress-strain curve of 1O-60CR alloy sample;
[0027] Figure 4 is Ti in Example 1 of the present invention 35 Zr 30 Nb 25 V 10 Room temperature tensile curve of -3O alloy sample;
[0028] Figure 5 is Ti in Example 2 of the present invention 35 Zr 30 Nb 25 V 10 -1O-90CR、Ti 35 Zr 30 Nb 25 V 10 -Room temperature tensile curve of 1.5O-90CR alloy sample;
[0029] Figure 6 is Ti in Example 3 of the present invention 35 Zr 30 Nb 25 V 10 -Tensile stress-strain curves of 1.5O-90CR alloy samples after tempering at 700℃ and 800℃ for 30min respectively;
[0030] Figure 7 is Ti in Example 3 of the present invention 35 Zr 30 Nb 25 V 10-Tensile stress-strain curves of 1.5O-90CR alloy samples after tempering at 500℃ for 30min;
[0031] Figure 8 is Ti in Example 3 of the present invention 35 Zr 30 Nb 25 V 10 Tensile stress-strain curves of -1.5O-90CR alloy samples after tempering at 1050℃ for 30min.
[0032] Fig. 9 It is the comparative example 1 of the present invention (NbTiZr) 93 Al 5 O 2 -Tensile stress-strain curves of 90CR alloy samples. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technicians in this field can make some non-essential improvements and adjustments to the present invention based on the above application content.
[0034] Example 1
[0035] The preparation method of the oxygen-doped TiZr-based single-phase refractory high-entropy alloy in this embodiment comprises the following steps:
[0036] Step 1: Follow Ti 35 Zr 30 Nb 25 V 10 The atomic ratios shown are 0at.%, 1at.% and 3at.% oxygen doped, respectively, and are denoted as Ti 35 Zr 30 Nb 25 V 10 、Ti 35 Zr 30 Nb 25 V 10 -1O and Ti 35 Zr 30 Nb 25 V 10 -3O sample, oxygen is passed through TiO 2 Incorporation in the form of TiO 2 The amount of added oxygen is determined by the amount of addition, and then, according to the TiO 2The content of four metal elements, Ti, Zr, Nb and V, was slightly adjusted accordingly according to the amount of addition. For each sample, a total mass of about 70g of raw materials was weighed out, and the purity of Ti, Zr, Nb and V particles was ≥99.95%;
[0037] Step 2: The weighed raw materials of each group of samples are melted in a high vacuum arc melting furnace in an argon atmosphere. The vacuum degree of the furnace chamber is first pumped to 6×10 -3 Pa, and then filled with argon to -0.05MPa. Each smelting was carried out at 330A current for 8min, and each group of samples was smelted at least five times.
[0038] Step 3: Smelting Ti 35 Zr 30 Nb 25 V 10 Sample, Ti 35 Zr 30 Nb 25 V 10 -1O samples and Ti 35 Zr 30 Nb 25 V 10 The -3O sample was cut into 10 mm × 10 mm × 2 mm blocks by wire cutting and ground to 2000 mesh using sandpaper. XRD test was performed at a speed of 0.033° / s with a measurement angle of 20°-90°.
[0039] Step 4: Prepare the Ti 35 Zr 30 Nb 25 V 10 The Ti-1O sample was divided into three parts by wire cutting. One part was not processed, and the other two parts were cut into flat cuboids. Then, they were cold rolled 2 times and 4 times at room temperature, respectively, so that the total thinning of the samples was 20% and 60%, respectively. The two groups of samples after cold rolling at room temperature were recorded as Ti 35 Zr 30 Nb 25 V 10 -1O-20CR、Ti 35 Zr 30 Nb 25 V 10 -1O-60CR.
[0040] The Ti obtained by smelting in step 2 35 Zr 30 Nb 25 V 10 Sample, Ti 35 Zr 30 Nb 25 V10 -1O samples and Ti 35 Zr 30 Nb 25 V 10 -3O sample, and Ti obtained by cold rolling deformation in step 3 35 Zr 30 Nb 25 V 10 -1O-20CR、Ti 35 Zr 30 Nb 25 V 10 -1O-60CR, standard tensile specimens were prepared by wire cutting and ground to 2000 mesh using sandpaper, and then tensile performance tests were performed on an Instron-5967 tensile machine at 1×10 -3 s -1 The strain rate is carried out and the stretching direction is along the rolling direction.
[0041] The results are as follows Figure 1-4 As shown, where:
[0042] Figure 1 Ti 35 Zr 30 Nb 25 V 10 , Ti 35 Zr 30 Nb 25 V 10 -1O and Ti 35 Zr 30 Nb 25 V 10 -3O sample's XRD results show that the addition of oxygen does not cause a change in the phase structure, and the alloys all maintain a single-phase body-centered cubic structure.
[0043] Figure 2 Ti 35 Zr 30 Nb 25 V 10 The room temperature tensile curve of Ti 35 Zr 30 Nb 25 V 10 The alloy sample has a tensile strength of about 850 MPa.
[0044] Figure 3 Ti with 1 at.% oxygen added 35 Zr 30 Nb 25 V 10 -1O alloy samples and Ti after 20% and 60% cold rolling deformation 35 Zr30 Nb 25 V 10 -1O-20CR、Ti 35 Zr 30 Nb 25 V 10 -1O-60CR alloy sample room temperature tensile curve. It can be seen from the figure that after adding 1at.% oxygen, Ti 35 Zr 30 Nb 25 V 10 The tensile strength of the -1O alloy sample reached 982MPa, while the plasticity did not decrease;
[0045] After different rolling deformation, Ti 35 Zr 30 Nb 25 V 10 -1O-20CR and Ti 35 Zr 30 Nb 25 V 10 -1O-60CR alloy samples have tensile strengths of 1240MPa and 1430MPa respectively. Even with a small rolling deformation, the strength is significantly improved, and Ti 35 Zr 30 Nb 25 V 10 -1O-20CR alloy sample has an elongation of 15%, Ti 35 Zr 30 Nb 25 V 10 The -1O-60CR alloy sample has an elongation of 12%. It can be seen that after oxygen doping combined with cold rolling deformation, the strength of the alloy is greatly improved while still maintaining an elongation of more than 10%.
[0046] Figure 4 Ti 35 Zr 30 Nb 25 V 10 -3O sample room temperature tensile curve, the sample produced brittle fracture, from which we can see that the content of doped oxygen should not be too high, the range should be 1at.%-2at.%.
[0047] Example 2
[0048] The preparation method of the oxygen-doped TiZr-based single-phase refractory high-entropy alloy in this embodiment comprises the following steps:
[0049] Step 1: Ti doped with 1 at.% oxygen 35 Zr 30 Nb 25 V10 -1O sample, and Ti doped with 1.5 at.% oxygen 35 Zr 30 Nb 25 V 10 -1.5O sample was mixed with raw materials, and the total mass of raw materials was about 70g, and the purity of Ti, Zr, Nb, and V particles was ≥99.95%.
[0050] Step 2: Melt the weighed raw materials in a high vacuum arc melting furnace in an argon atmosphere. First, draw the vacuum degree of the furnace chamber to 6×10 -3 Pa, then filled with argon to -0.05MPa. Each melting was carried out for 8min at 330A current, and each sample was melted at least five times.
[0051] Step 3: Prepare the Ti 35 Zr 30 Nb 25 V 10- 1O samples and Ti 35 Zr 30 Nb 25 V 10 The Ti-1.5O samples were cut into flat cuboids by wire cutting, and then cold rolled for 6 times at room temperature to reduce the total thinning amount of the samples by 90%. The samples after cold rolling at room temperature were recorded as Ti 35 Zr 30 Nb 25 V 10 -1O-90CR and Ti 35 Zr 30 Nb 25 V 10 -1.5O-90CR.
[0052] Ti 35 Zr 30 Nb 25 V 10 -1O-90CR、Ti 35 Zr 30 Nb 25 V 10 -1.5O-90CR were prepared by wire cutting to prepare standard tensile specimens, sanded to 2000 mesh, and then subjected to tensile performance tests. The tensile tests were performed on an Instron-5967 tensile machine at 1×10 -3 s -1 The strain rate is carried out and the stretching direction is along the rolling direction.
[0053] The results are as follows Figure 5 As shown, Ti 35 Zr 30 Nb 25V 10 -1O and Ti 35 Zr 30 Nb 25 V 10 After 90% rolling deformation, Ti 35 Zr 30 Nb 25 V 10 -1O-90CR has a tensile strength of 1595MPa, Ti 35 Zr 30 Nb 25 V 10 The tensile strength of -1.5O-90CR reaches 1750MPa, which is 88% and 106% higher than the original sample, and has an elongation of 12% and 10% respectively. By increasing the doped oxygen content and increasing the cold rolling deformation, a refractory high entropy alloy with ultra-high strength was successfully prepared.
[0054] Example 3
[0055] The preparation method of the oxygen-doped TiZr-based single-phase refractory high-entropy alloy in this embodiment comprises the following steps:
[0056] Step 1: Ti doped with 1.5 at.% oxygen 35 Zr 30 Nb 25 V 10 -1.5O sample was used for raw material proportioning, and the total mass of raw materials was weighed out to be about 70g, and the purity of Ti, Zr, Nb, and V particles was ≥99.95%.
[0057] Step 2: Melt the weighed raw materials in a high vacuum arc melting furnace in an argon atmosphere. First, draw the vacuum degree of the furnace chamber to 6×10 -3 Pa, and then filled with argon to -0.05MPa. Each smelting was carried out at 330A current for 8min, and the sample was smelted at least five times.
[0058] Step 3: Prepare the Ti 35 Zr 30 Nb 25 V 10 The -1.5O sample was cut into flat cuboids by wire cutting, and the total thinning amount of the sample was 90% by cold rolling deformation at room temperature for 6 times, and then divided into four parts by wire cutting.
[0059] Step 4: one of the samples obtained in step 3 is kept at 500°C for 30 min and then quenched, one is kept at 700°C for 30 min and then quenched, one is kept at 800°C for 30 min and then quenched, and the other is kept at 1050°C for 30 min and then quenched. The heat treatment process is carried out in a tubular furnace with an argon atmosphere.
[0060] The sample obtained by the medium temperature tempering treatment in step 4 was prepared into a standard tensile specimen by wire cutting, and then sanded to 2000 mesh. Then, the tensile performance test was performed on an Instron-5967 tensile machine at 1×10 -3 s -1 The strain rate is carried out and the stretching direction is along the rolling direction.
[0061] The results are as follows Figure 6-8 As shown, where:
[0062] Figure 6 Ti 35 Zr 30 Nb 25 V 10 The room temperature tensile curves of the -1.5O sample after 90% rolling deformation and tempering at 700℃ and 800℃ respectively. The tensile strength of the 700℃ tempered sample reached 1400MPa and had an elongation of 14%; the 800℃ tempered sample had a tensile strength of 1350MPa and an elongation of 22%, which has a better combination of strength and plasticity than most refractory high entropy alloys. On the contrary, Figure 7 The sample tempered at 500℃ produced brittle fracture. Low-temperature tempering will cause the alloy to become brittle, which is not conducive to the improvement of mechanical properties. Figure 8 The strength of the sample tempered at 1050℃ is greatly reduced, and high temperature tempering will lead to a significant reduction in the strengthening effect.
[0063] Comparative Example 1
[0064] The preparation method of the oxygen-doped TiZr-based single-phase refractory high entropy alloy in this comparative example comprises the following steps:
[0065] Step 1: (NbTiZr) 93 Al 5 O 2 The raw materials of the sample were proportioned, and the total mass of raw materials of about 70g was weighed out respectively, and the purity of Ti, Zr, Nb, and Al particles was ≥99.95%.
[0066] Step 2: Melt the weighed raw materials in a high vacuum arc melting furnace in an argon atmosphere. First, draw the vacuum degree of the furnace chamber to 6×10 -3 Pa, and then filled with argon to -0.05MPa. Each smelting was carried out for 8 minutes at 330A current, and each sample was smelted at least five times.
[0067] Step 3: Prepare (NbTiZr) in step 2 93 Al 5 O 2 The sample was cut into two parts by wire cutting, one part was cut into a flat cuboid, and then the total thinning amount of the sample was 90% by cold rolling deformation at room temperature for 6 times. The sample after cold rolling deformation at room temperature was recorded as (NbTiZr) 93 Al 5 O 2 -90CR.
[0068] (NbTiZr) 93 Al 5 O 2 and (NbTiZr) 93 Al 5 O 2 -90CR were prepared by wire cutting to prepare standard tensile specimens, sanded to 2000 mesh, and then subjected to tensile performance tests. The tensile test was performed on an Instron-5967 tensile machine at 1×10 -3 s -1 The strain rate is carried out and the stretching direction is along the rolling direction.
[0069] The results are as follows Fig. 9 As shown, (NbTiZr) 93 Al 5 O 2 The tensile strength of NbTiZr reaches 1140MPa, while the strength of NbTiZr is usually around 700MPa. This shows that replacing V with Al and doping with oxygen can also achieve a good strengthening effect; after 90% cold deformation, the strength reaches 1500MPa, which greatly breaks through the strength limit of NbTiZr. This also shows that the present invention is not limited to the four elements of Nb, Ti, V, and Zr, and has a good effect on TiZr-based high entropy alloys.
[0070] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An oxygen-doped TiZr-based single-phase refractory high-entropy alloy, characterized in that: The oxygen-doped TiZr-based single-phase refractory high-entropy alloy includes Ti, Zr, Nb, V and O elements, wherein the sum of the atomic contents of Ti, Zr, Nb and V elements is equal to 100%, and the atomic contents of Ti, Zr, Nb and V elements satisfy Ti≥Zr>Nb>V.
2. The oxygen-doped TiZr-based single-phase refractory high-entropy alloy according to claim 1, characterized in that: The Ti, Zr, Nb and V elements are calculated in atomic percentage, with Ti element being 25 at.%-40 at.%, Zr element being 25 at.%-40 at.%, Nb element being 15 at.%-30 at.%, and V element being 5 at.%-15 at.%.
3. The oxygen-doped TiZr-based single-phase refractory high-entropy alloy according to claim 1, characterized in that: The doping method of the O element is to add it in the form of TiO2, and the atomic content of the O element added to the alloy is 1at.%-2at.%.
4. The oxygen-doped TiZr-based single-phase refractory high-entropy alloy according to claim 1, characterized in that: The oxygen-doped TiZr-based single-phase refractory high-entropy alloy is obtained by first smelting raw materials containing Ti, Zr, Nb, V and O elements to obtain an alloy ingot, and then performing large plastic deformation treatment and medium-temperature tempering treatment on the alloy ingot.
5. A method for preparing the oxygen-doped TiZr-based single-phase refractory high-entropy alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Design the atomic content of each element Ti, Zr, Nb, V and the atomic content of the doped O element in the alloy, and then weigh the raw materials according to the designed atomic content of each chemical element; Step 2: Smelting the raw materials weighed in step 1 to obtain an oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot; Step 3: performing large plastic deformation treatment on the oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot obtained in step 2; Step 4: performing medium-temperature tempering treatment on the oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot obtained by the treatment in step 3.
6. The method for preparing an oxygen-doped TiZr-based single-phase refractory high-entropy alloy according to claim 5, characterized in that: Specifically, the step three is to first cut the oxygen-doped TiZr-based single-phase refractory high-entropy alloy ingot into a rectangular shape by wire cutting to obtain a rectangular alloy sample, and then perform a small amount of multiple cold rolling deformation treatments on the rectangular alloy sample at room temperature, with each deformation amount not exceeding 20%.
7. The method for preparing an oxygen-doped TiZr-based single-phase refractory high-entropy alloy according to claim 6, characterized in that: In the step 3, the total thinning amount of the sample after cold rolling deformation is 20%-90% of the thickness of the original sample.
8. The method for preparing an oxygen-doped TiZr-based single-phase refractory high-entropy alloy according to claim 5, characterized in that: In the step 4, the temperature range of the medium-temperature annealing treatment is 600° C.-800° C., and the time is 10 min-30 min.
Citation Information
Patent Citations
Hyperelastic TiZrHfNbAl high-entropy alloy and manufacturing methods thereof
CN107419154A
High-specific-strength high-plasticity refractory high-entropy alloy and preparing method thereof
CN108677077A
High-strength and high-toughness TiZrNbV series high-entropy alloy with ordered oxygen complex and preparation method of high-strength and high-toughness TiZrNbV series high-entropy alloy
CN116770150A
Method for processing ingot and apparatus for processing ingot
KR1020220167223A
High-entropy alloy and method for heat-treating same
WO2021261609A1